Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.14440/bladder.2018.565
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2D and 3D ultrasound methods to measure serial bladder volumes during filling: Steps toward development of non-invasive ultrasound urodynamics

Abstract: Objectives: Non-invasive methods to objectively characterize overactive bladder (OAB) and other forms of voiding dysfunction using real-time ultrasound are currently under development but require accurate and precise serial measurements of bladder volumes during filling. This study’s objective was to determine the most accurate and precise ultrasound-based method of quantifying serial bladder volumes during urodynamics (UD).Methods: Twelve female participants with OAB completed an extended UD procedure with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…However, classifying bladder shape and memorizing appropriate coefficients are both difficult and impractical for calculating bladder volume during each ultrasound examination. Nagle et al [27] reported that automated 3D scanning ultrasound with manual tracing of the bladder outline provided the most precise nonuniform bladder geometry. However, compared with the 2D diameter method, manually tracing the bladder outline on 12 images is more time-consuming.…”
Section: Discussionmentioning
confidence: 99%
“…However, classifying bladder shape and memorizing appropriate coefficients are both difficult and impractical for calculating bladder volume during each ultrasound examination. Nagle et al [27] reported that automated 3D scanning ultrasound with manual tracing of the bladder outline provided the most precise nonuniform bladder geometry. However, compared with the 2D diameter method, manually tracing the bladder outline on 12 images is more time-consuming.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound technology's ability to visualize the bladder and prostate helps in the identification of several issues, such as intravesical prostate prominence or detrusor muscle diameter, and in revealing the presence of diverticula (small pockets that can develop in the bladder wall and stones that can cause blockages and pain) [39][40][41][42].…”
Section: Ultrasound Technologymentioning
confidence: 99%
“…The first wearable ultrasound device for bladder monitoring was developed by Petrican et al in 1998 [43]; since that time, the easy accessibility to commercial portable ultrasound devices, combined with the fact that the technology is non-invasive, safe, and painless, makes it one of the optimal BUV monitoring modalities [22,37,44]. Ultrasound technology's ability to visualize the bladder and prostate helps in the identification of several issues, such as intravesical prostate prominence or detrusor muscle diameter, and in revealing the presence of diverticula (small pockets that can develop in the bladder wall and stones that can cause blockages and pain) [39][40][41][42].…”
Section: Ultrasound Technologymentioning
confidence: 99%
“…3b). 3D integration, Virtual Organ Computed-aided AnaLysis (VOCAL software), rendering techniques, and other volume reconstruction techniques have been proposed to this purpose [104], [105], [106], [107], [108]. 3D reconstruction of bladder volume has shown promising results in the diagnosis of voiding dysfunctions [105].…”
Section: ) Ultrasound Imagingmentioning
confidence: 99%
“…3D integration, Virtual Organ Computed-aided AnaLysis (VOCAL software), rendering techniques, and other volume reconstruction techniques have been proposed to this purpose [104], [105], [106], [107], [108]. 3D reconstruction of bladder volume has shown promising results in the diagnosis of voiding dysfunctions [105]. Marks et al have evaluated the use of the technique for defining when to catheterize the patient, comparing the volume estimated with the 3D reconstruction technique and the volume of urine excreted by catheterization (defined as the real volume).…”
Section: ) Ultrasound Imagingmentioning
confidence: 99%